Czech Republic : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report, 2002)
This Selected Issues paper and Statistical Appendix describes developments in the Czech labor market since 1995 and examines forces underlying these developments. The main focus of the paper is on how the characteristics of unemployment and employment have been changing, and how the changes are related to the transformation of the economy. It suggests that not all changes are for the worse, but a number of worrisome tendencies have emerged that could undermine the Czech Republic's medium-term growth.